2014
DOI: 10.1080/10408398.2011.653018
|View full text |Cite
|
Sign up to set email alerts
|

The Growing Role of Front-of-Pack Nutrition Profile Labeling: A Consumer Perspective on Key Issues and Controversies

Abstract: Nutrition-related diseases, such as some cancers, heart diseases, and obesity, belong to the most challenging health concerns of our time. Communicating intuitive and simple nutrition information by means of front-of-pack (FOP) nutrition profile signpost labeling is increasingly seen as an essential tool in efforts to combat unhealthy food choices and improve public health. Consequently, much attention in policy and research is given to nutrient profiling methods and the determination of optimal nutrition crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
135
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(145 citation statements)
references
References 95 publications
1
135
0
9
Order By: Relevance
“…In contrast to health claims, FoPLs are considered to provide more of a comprehensive, balanced summary of a food’s healthiness [36]. Multiple FoPLs can and often do exist in a marketplace.…”
Section: Front-of-pack Labelsmentioning
confidence: 99%
“…In contrast to health claims, FoPLs are considered to provide more of a comprehensive, balanced summary of a food’s healthiness [36]. Multiple FoPLs can and often do exist in a marketplace.…”
Section: Front-of-pack Labelsmentioning
confidence: 99%
“…FOP nutrition labels highlight a few key nutrients but often do so using more than text. Research on FOP nutrition labels has shown that nearly all labels use pictorial or symbolic elements to convey meaning because they are recognized more readily than words (Van Kleef & Dagevos, 2013) and that labels that combine short text claims, graphics, and color are the most effective. Designed this way, these labels are more likely to receive attention when the consumer is under time pressure (Van Herpen & Van Trijp, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical evidence on the effect of information on behavior in various fields of (intertemporal) decision making is mixed, but most studies fail to find a convincing effect. When it comes to food information, Van Kleef and Dagevos (2012) (2008,2011) comes to a similar conclusion: it may even be counterproductive.…”
Section: Supervisors (Iops)mentioning
confidence: 83%